RISIKO PENULARAN PENYAKIT TUBERKULOSIS KEPADA KELUARGA KONTAK SERUMAH MELALUI ASPEK KESEHATAN GIGI DI WILAYAH KERJA PUSKESMAS PADASUKA KOTA BANDUNG - Fitriyani, Annisa Fuzzi; Laela, Dewi Sodja; Utami, Ulfah (Poltekkes Kemenkes Bandung, 2024)
Pulmonary tuberculosis (TB) transmission can occur indoors via airborne droplets containing TB bacteria. Household contacts are at increased risk of infection. Sharing toothbrushes or storing them in close proximity can lead to cross-infection. This study aimed to identify risk factors for TB transmission among close household contacts through dental hygiene practices. A qualitative descriptive approach was employed, utilizing in-depth face-to-face interviews and observations. Three BTA- positive patients were recruited as subjects. The study variable was risk factors for TB transmission to close household contacts through dental hygiene practices. Findings revealed that BTA-positive patients had a habit of storing toothbrushes together with family members and had close contact with positive household members. Storing toothbrushes together with bristles touching can facilitate cross- infection. Sharing and storing toothbrushes in close proximity increases the risk of TB cross-infection. Proper toothbrush storage and usage, particularly among TB patients, are crucial to prevent cross-infection via contaminated bristles.